Identificamos un periódico mural y conocemos su estructura e importancia - Andrade Rodriguez, Kevin Alexander (2019)
The present professional sufficiency work entitled “Identify a mural, we know its structure and importance.” will be developed in the experimental Educational center “ Rafael Narváez Cadenillas”, located in The city of Trujillo. It has been designed for 2nd grade students._x000D_ The principal aim of the social constructivism is, through the group work, students develop the reading and writing skills, in order to they will be able to write different types of texts in your mother tongue._x000D_ furthermore, the teacher provides a quality learning environment. He encourages the students to participate during the whole class to achieve meaningful learning through the use of teaching materials to make the classroom session more didactic.